The Inheritance of Malay Palace Dance in Malaysia and Yogyakarta Classical Dance in Indonesia - Taib Bin Saearani, Muhammad Fazli; Cahyono, Agus (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2016)
The background of this study is the effort of solving the inheritance problem faced by Malaysia in the case of Malay Palace dance which is currently in decline. This study is done by using best practice from the The Development and Inheritance of Yogyakarta Classical Dance (TKGY) done by the Ngayogyakarta Hadiningrat Palace and some formal and non-formal institutions in Yogyakarta, Indonesia. TKGY is chosen as it is viewed to have positive life in classical Palace dance and involve various actors and clear strategies. For three years, the researcher has done the research by observing the inheritance context (TKGY) to identify preservation phenomena done in Yogyakarta. This research is using a qualitative approach. The data are collected by doing in-depth interviews with some leaders of the main studios in Yogyakarta and Malay Palace dance choreographers in Malaysia. The result of the research shows that there are some similarities and differences between Malay palace dance in Malaysia and Yogyakarta classical dance. Some strategies have been used to describe how the Malaysian government adopts inheritance strategies (TKGY) used by actors in the inheritance discourse (TKGY).How to Cite: Saearani, M. F. T. B & Cahyono, A. (2016). The Inheritance of Malay Palace Dance in Malaysia and Yogyakarta Classical Dance in Indonesia . Harmonia: Journal of Arts Research And Education, 16(1), 75-86. doi:http://dx.doi.org/10.15294/harmonia.v16i1.6145Â